Learning from Asian and Indo-Pacific fisheries history - HOLM, POUL (Springer Science+Business Media, 2014)
Until recently very little had been published on the history of Asian fisheries. This sorry state of neglect changed at one stroke with the publication of Butcher's 2004 study of South East Asian fisheries. The present volume demonstrates the breadth and depth of progress in recent years. It is high time that historians from outside the region take note and reconsider some of our well-established patterns of thought in light of what we may learn from these new perspectives.
Historical Perspectives of Fisheries Exploitation in the Indo-Pacific
Keywords: Fisheries; Asia; Identities in Transformation; Smart & Sustainable Planet